Immunoexpression of cell cycle biomarkers in neuroblastoma samples and its correlation with prognostic factors Imunoexpressão de biomarcadores do ciclo celular em amostras de neuroblastomas e sua relação com fatores prognósticos - Lúcia de Noronha; Deli Grace de Barros Araújo; Priscilla do Carmo Gozzo; Luana E. Harada; Ana Paula Percicote; Seigo Nagashima; Elisabeth Schneider Gugelmin; Flora Watanabe; Milton Marcio Machota Junior; Isabela Werneck da Cunha (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: It is widely known that the expression levels of molecules involved in apoptosis regulation and cell proliferation have prognostic value in patients with neuroblastomas. OBJECTIVE: To determine the expression of Ki67, B-cell lymphoma 2 (BCL-2), phosphatase and tensin homolog (PTEN), BCL-2 associated protein X (BAX) and caspase-8 proteins in neuroblastomas and to propose new prognostic biomarkers that could enable a better classification of risk groups. MATERIAL AND METHODS: Formalin fixed paraffin embedded neuroblastoma samples (n = 23) were arranged into tissue microarray blocks and analyzed by immunohistochemistry. The patients were classified according to clinical and pathological prognostic factors (age, site, presence or absence of bone-marrow infiltration, poorly or well differentiated ganglioneuroblastoma, Schwannian stroma rich or poor, favorable or unfavorable Shimada histology, and presence or absence of MYCN oncogene amplification) and clinical course (with or without fatal outcome, with or without relapses/residual lesion). RESULTS: Twelve patients were female; nine children were over 18 months old; nine had extra-abdominal tumors; nine had tumors with unfavorable histology. Fifteen patients underwent bone-marrow biopsy and four were positive for metastasis. Nine patients progressed to fatal outcome. CONCLUSION: Ki67 immunoexpression was lower in cases of Schwannian-stroma rich neuroblastomas (p = 0.018) and higher in poorly differentiated cases (p = 0.013). PTEN was less positive in stroma rich neuroblastomas (p = 0.024). Caspase-8 was more immunopositive in cases of negative bone marrow infiltration (p = 0.035). Therefore, these biomarkers could be applied to discriminate groups with poor prognosis. INTRODUÇÃO: Sabe-se que os níveis de expressão de moléculas envolvidas na regulação da apoptose e da proliferação celular apresentam valor prognóstico em pacientes com neuroblastomas. OBJETIVO: Avaliar a imunoexpressão das proteínas Ki67, B-cell lymphoma 2 (BCL-2), phosphatase and tensin homolog (PTEN), caspase-8 e BCL-2 associated protein X (BAX) em neuroblastomas na tentativa de propor novos biomarcadores prognósticos que poderiam auxiliar na melhor discriminação dos grupos de risco. MATERIAL E MÉTODOS: Amostras de neuroblastoma (n = 23) foram submetidas à técnica tissue microarray e analisadas com imuno-histoquímica. Os pacientes foram classificados de acordo com os fatores prognósticos clínico-patológicos (idade, localização, medula óssea infiltrada ou não, pouco diferenciado ou em diferenciação/ganglioneuroblastoma, rico ou pobre em estroma com células de Schwann, histologia favorável ou desfavorável segundo Shimada, presença ou não da amplificação do MYCN) e com o curso clínico (se em óbito ou vivo, com ou sem lesão residual/recidiva). RESULTADOS: Doze casos eram do sexo feminino; nove tinham idade acima de 18 meses; nove apresentavam tumores extra-abdominais; e nove cursavam com histologia desfavorável. Quinze pacientes foram submetidos à biópsia de medula óssea, sendo quatro com apresentação de metástase. Nove pacientes evoluíram ao óbito. CONCLUSÃO: A imunoexpressão do Ki67 foi mais baixa nos casos ricos em estroma (p = 0,018) e elevada nos casos pouco diferenciados (p = 0,013). O PTEN apresentou-se menos positivo em neuroblastomas ricos em estroma (p = 0,024). A caspase-8 foi mais imunopositiva em casos com medula óssea negativa (p = 0,035). Esses biomarcadores poderiam ser utilizados para auxiliar a discriminar grupos de pacientes de pior prognóstico.